A rapid replication method for liquid metal microstructure prepared by electrohydrodynamic jet printing

CN122788409BActive Publication Date: 2026-10-23DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611283312.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-23
Estimated Expiration
2046-08-24

AI Technical Summary

Technical Problem

[0007]在传统转移印刷过程中,当施加较大的界面粘附力或提高剥离速率时,液态金属表面的氧化膜容易发生撕裂,导致内部液态金属流动、结构收缩或图案失真;而当界面粘附力不足时,又难以实现有效转移

Benefits of technology

[0026]本申请提出的方法通过在基底上预制液态金属微米结构母版,利用液态金属微米结构母版自身核壳结构的物理特性及界面结合力的差异,实现微米结构的“内部断裂复制”,不仅完美保留了原结构的分辨率,更能实现对同一液态金属微米结构母版的连续复制。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122788409B_ABST
    Figure CN122788409B_ABST
Patent Text Reader

Abstract

The application discloses a kind of liquid metal microstructure rapid replication methods for electrofluidic jet printing preparation.First, the method utilizes electrohydrodynamic jet printing technology to prepare liquid metal microstructure master on substrate;Subsequently, viscous stretch medium is covered and pressed on the surface of liquid metal microstructure master, and then is stripped at a specific angle and speed.The principle that the adhesion of viscous stretch medium is greater than the combined force of the oxide film shell layer of liquid metal microdroplet in the liquid metal microstructure master and the internal liquid metal microdroplet, but less than the combined force of the liquid metal microstructure master and substrate, realizes the internal fracture type replication of liquid metal, to obtain high-fidelity replication structure on viscous stretch medium, while the master is completely retained on the substrate, and can be continuously replicated for many times after being solidified again.The application solves the problem that traditional transfer printing technology is difficult to be applied to liquid metal microstructure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of advanced manufacturing technology, specifically relating to a rapid replication method for liquid metal microstructures prepared by electrohydraulic inkjet printing. Background Technology

[0002] Gallium-based liquid metals, possessing both the high electrical and thermal conductivity of metals and the deformability of liquids, show great promise for applications in flexible electronics, wearable devices, soft robots, radio frequency antennas, and microsensors. Compared to traditional solid metals, liquid metals can maintain continuous conductivity even under large deformation conditions, thus being considered important functional materials for building next-generation flexible electronic systems.

[0003] In recent years, electrohydrodynamic printing has been widely used in the fabrication of liquid metal microstructures due to its advantages such as high resolution, non-contact deposition, and wide material adaptability. This technology utilizes the electric field force generated by a high-voltage electric field to overcome the surface tension of the liquid, causing the tip of the nozzle to form a stable Taylor cone and generate a fine jet, thereby directly constructing micron-scale conductive structures on the substrate surface. Compared to traditional inkjet printing, electrohydrodynamic printing can achieve higher processing accuracy and smaller structural dimensions.

[0004] However, for electronic devices requiring large-area, high-density repeating patterns, electrofluid printing remains a point-by-point, line-by-line construction process, significantly limiting its manufacturing efficiency. When large quantities of identical micron-sized structures need to be fabricated, repeated printing significantly increases equipment downtime and production costs. Therefore, there is an urgent need to develop a manufacturing method that can rapidly replicate existing liquid metal microstructure master templates.

[0005] Currently, large-area replication of micro and nanostructures mainly employs transfer printing techniques, including elastomer stamp transfer, microcontact printing, rate-controlled transfer printing, and transfer processes based on sacrificial layer release. These methods typically utilize the differences in interfacial adhesion between the stamp and the structure, and between the structure and the target substrate, to achieve structure transfer by controlling contact pressure, peel speed, or interfacial energy. They have been widely applied in the fabrication of semiconductor thin films, metal thin films, and polymer microstructures.

[0006] However, the aforementioned transfer printing technology is mainly aimed at solid structures with stable mechanical strength, and its transfer process relies on the continuity and integrity of the overall structure. Gallium-based liquid metal microstructures differ fundamentally from traditional solid-state microstructures: when liquid metal is exposed to air, an oxide film shell with a thickness of approximately 0.5–3 nm instantly forms on its surface, creating a unique core-shell structure of "oxide film shell – liquid metal core." This oxide film shell can maintain the stability of the microstructure morphology, but its mechanical strength is far lower than that of traditional solid structures, while the internal liquid metal possesses fluidity and reconfigurability.

[0007] In traditional transfer printing, when applying strong interfacial adhesion or increasing the peeling rate, the oxide film on the liquid metal surface is prone to tearing, leading to internal liquid metal flow, structural shrinkage, or pattern distortion. Conversely, insufficient interfacial adhesion makes effective transfer difficult. Therefore, existing transfer printing technologies based on interfacial adhesion differences struggle to simultaneously meet the requirements of high-fidelity replication of liquid metal microstructures and complete master plate preservation. This is especially true for high-resolution micron-sized structures prepared by electrohydraulic inkjet printing, whose linewidths are typically only tens to hundreds of micrometers, making them more susceptible to breakage, deformation, and master plate damage during the transfer process.

[0008] Therefore, it is of great scientific significance and practical value to provide a method that can utilize the physical properties of liquid metal to achieve high-fidelity, low-cost, and continuous replication of liquid metal microstructures without damaging the high-precision master structure, thereby promoting the application of liquid metal in electronic devices. Summary of the Invention

[0009] The purpose of this invention is to overcome the shortcomings of the prior art and provide a rapid replication method for liquid metal microstructures prepared by electrohydraulic inkjet printing.

[0010] To achieve the above objectives, some embodiments of the present invention provide the following technical solutions: A rapid replication method for liquid metal microstructures prepared by electrofluidic inkjet printing includes the following steps: preparing a liquid metal ink for electrofluidic inkjet printing, wherein the liquid metal ink is a mixture of liquid metal, polymer, and solvent; depositing the liquid metal ink onto a substrate surface using a non-contact deposition method of electrofluidic inkjet printing, wherein the substrate moves with a spindle to form a liquid metal microstructure with a preset pattern, wherein the liquid metal microstructure includes liquid metal droplets, and the spaces between the liquid metal droplets are filled with the polymer and the solvent; and placing the substrate containing the liquid metal microstructure at room temperature for a period of time to solidify it to obtain a liquid metal microstructure master template, wherein during the solidification process, at least a portion of the solvent evaporates, and each liquid metal droplet forms an oxide film shell on the surface, the oxide film... The polymer exists between the shell layers; then, a viscous stretching medium is covered and adhered to the upper surface of the liquid metal microstructure master plate, and a preset pressure is applied to the adhered viscous stretching medium to make the viscous stretching medium tightly adhere to the oxide film shell layer of the top liquid metal microdroplets in the liquid metal microstructure master plate; finally, the viscous stretching medium is peeled off from the surface of the liquid metal microstructure master plate, so that the oxide film shell layer of the top liquid metal microdroplets is destroyed, thereby obtaining the oxide film shell layer and a part of the liquid metal microstructure master plate with the preset pattern on the surface of the viscous stretching medium, that is, a replicated liquid metal microstructure with a continuous network morphology, while the remaining part of the liquid metal microstructure master plate retained on the substrate surface also has the preset pattern.

[0011] The replication operation consists of the following steps: covering and adhering a viscous stretching medium to the surface of the liquid metal microstructure master plate; applying a preset pressure to the adhered viscous stretching medium to make it adhere tightly to the surface of the liquid metal microstructure master plate; and finally peeling the viscous stretching medium off the surface of the liquid metal microstructure master plate.

[0012] In some embodiments, before covering and adhering the calibrated viscous stretching medium to the surface of the oxide film shell, the relationship between the selection of the viscous stretching medium, the preset pressing pressure, the preset pressing time, the preset peeling speed, and the preset peeling angle and the peeling force is calibrated such that the viscous stretching medium, the preset pressing pressure, the preset pressing time, the preset peeling speed, and the preset peeling angle are sufficient to overcome the bonding force between the liquid metal droplets in the liquid metal microstructure master and the oxide film shell during the replication operation, but less than the bonding force between the liquid metal microstructure master and the substrate.

[0013] Preferably, the predetermined viscous stretching medium, the predetermined pressing force, the predetermined pressing time, the predetermined peeling speed, and the predetermined peeling angle cause the peeling force generated by the liquid metal microstructure master during the replication operation to be greater than 20% of the bonding force between the liquid metal droplets in the liquid metal microstructure master and the oxide film shell, but less than 20% of the bonding force between the liquid metal microstructure master and the substrate.

[0014] In some embodiments, the liquid metal ink contains 20% EGaIn liquid metal by mass, 5% polymer by mass, and the remainder is solvent; the solvent is composed of EG, propylene glycol, and water.

[0015] Preferably, the Ga:In ratio in the EGaIn liquid metal is 3:1 to 4:1 wt%; and the viscosity of the polymer is 1 to 10 cP.

[0016] Preferably, the EGaIn liquid metal is first ultrasonically dispersed in a solvent for 5 minutes to ensure uniform distribution of the EGaIn liquid metal in the solvent, the polymer is added and dissolved in the solvent, and the two are mixed and stirred for 24 hours.

[0017] Preferably, the voltage applied in the electrohydraulic inkjet printing method is direct current, with a voltage range of 2.5kV to 4kV, so that the tip of the nozzle forms a stable Taylor cone.

[0018] Preferably, the height of the tip of the spray needle from the substrate is in the range of 0.2mm to 3mm.

[0019] Preferably, the inner diameter of the nozzle is 100μm~150μm, and the linewidth of the prepared liquid metal microstructure is 70μm~300μm.

[0020] Preferably, the solidification time of the liquid metal microstructure is 20 min to 40 min.

[0021] Preferably, the viscous stretching medium includes hot melt adhesive tape, polyurethane tape, polyethylene tape, or polyimide tape, i.e., PI tape, which is made of polyimide film and silicone adhesive, can withstand temperatures of 260℃~300℃, and has a tape thickness of 0.055mm.

[0022] Preferably, the pressing force is 0.01~0.1MPa, and the cumulative pressing time is 10~50s; the pressing force can be precisely controlled by a force sensor.

[0023] Preferably, the angle between the viscous stretching medium and the substrate during peeling is 30° to 70°. When the peeling angle is greater than 70°, the excessive vertical pulling force will cause the liquid metal microstructure master plate to be partially lost; when it is less than 30°, if it is a flexible substrate, the lateral shear force will easily cause the substrate to deform.

[0024] Preferably, the peeling speed of the viscous stretching medium is 5 mm / s to 10 mm / s.

[0025] In some embodiments, the adhesion and peeling steps are repeated on the remaining portion of the liquid metal microstructure master remaining on the substrate to achieve multiple consecutive replications of the liquid metal microstructure.

[0026] The method proposed in this application prefabricates a liquid metal micron structure master on a substrate and utilizes the physical properties of the core-shell structure of the liquid metal micron structure master and the difference in interfacial bonding force to achieve "internal fracture replication" of the micron structure. This not only perfectly preserves the resolution of the original structure but also enables continuous replication of the same liquid metal micron structure master.

[0027] The beneficial effects of this invention specifically include: The embodiments of this invention utilize the physical properties of liquid metal forming an "oxide film shell + fluid internal closure" in air. By precisely adjusting the adhesive force of the viscous stretching medium, the metal oxide film shell formed by the liquid metal is broken, causing "fracture" to occur inside the liquid metal. This replication method not only obtains high-resolution target patterns but also makes the micron-structure of the liquid metal less susceptible to damage.

[0028] Because the liquid metal master structure described in this invention is retained on the substrate, the residual fresh liquid metal surface layer will quickly reform a new oxide film shell in the air. Through simple and repeated "solidification-adhesion-peeling" operations, multiple replicas can be derived from a single master, greatly reducing the manufacturing cost and time cycle of high-precision electronic devices and achieving efficient continuous batch manufacturing. Attached Figure Description

[0029] Figure 1 This is a schematic diagram of the actual operation of the rapid replication method for liquid metal microstructures prepared by electrofluid inkjet printing according to the present invention. Figure 2 This is a SEM image of the liquid metal micron structure master template in Embodiment 1 of the present invention; Figure 3 This is a SEM image of the liquid metal micron structure on the PI tape after the first replication operation in Embodiment 1 of the present invention; Figure 4 This is a schematic diagram of the liquid metal micron structure obtained in the second replication operation in Embodiment 1 of the present invention; Figure 5 This is a schematic diagram of the liquid metal microstructure replicated after applying excessive pressure in Embodiment 3 of the present invention.

[0030] In the figure, 100 is the master template of the liquid metal microstructure, 200 is the PI tape, 300 is the replicated liquid metal microstructure, and 400 is the defect. Detailed Implementation

[0031] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and technical solutions.

[0032] As summarized above, this application proposes a rapid replication method for liquid metal microstructures prepared by electrohydraulic inkjet printing. The method first prepares a liquid metal ink for electrohydraulic inkjet printing, which is a mixture of liquid metal droplets, a polymer, and a solvent. The liquid metal ink is then fed into a nozzle using a microfluidic pump, and a voltage is applied to the tip of the nozzle to shear and refine the jet. Next, using a non-contact deposition method of electrohydraulic inkjet printing, the liquid metal ink is deposited onto a substrate surface. The substrate moves with the main axis to form a liquid metal microstructure with a preset pattern, wherein the liquid metal microstructure includes liquid metal droplets, and the spaces between the liquid metal droplets are filled with a polymer and a solvent. The substrate containing the liquid metal microstructure is then left at room temperature for a period of time to solidify, resulting in a liquid metal microstructure master 100. During the solidification process, at least a portion of the solvent evaporates, and each of the liquid metal droplets... A liquid metal microdroplet forms an oxide film shell on its surface, with the polymer layer between the oxide film shells. A viscous stretching medium is then applied to the upper surface of the liquid metal microstructure master 100. A preset pressure is applied to the adhered viscous stretching medium, causing it to adhere tightly to the oxide film shell of the top layer of liquid metal microdroplets in the liquid metal microstructure master 100. Finally, the viscous stretching medium is peeled off from the surface of the liquid metal microstructure master 100, destroying the oxide film shell of the top layer of liquid metal microdroplets. This results in the oxide film shell and a portion of the liquid metal microstructure master 100 with the preset pattern on the surface of the viscous stretching medium, i.e., a replicated liquid metal microstructure 300 with a continuous network morphology. The remaining portion of the liquid metal microstructure master 100 retained on the substrate surface also retains the preset pattern.

[0033] The replication operation consists of the following steps: covering and adhering a viscous stretching medium to the surface of the liquid metal microstructure master plate; applying a preset pressure to the adhered viscous stretching medium to make it adhere tightly to the surface of the liquid metal microstructure master plate; and finally peeling the viscous stretching medium off the surface of the liquid metal microstructure master plate.

[0034] In some embodiments, before covering and adhering the viscous stretching medium to the surface of the liquid metal microstructure master 100, the relationship between the selection of the viscous stretching medium, the pressing pressure, the pressing time, the peeling speed, and the peeling angle and the peeling force is calibrated to obtain relevant calibration curves. This ensures that the determined preset viscous stretching medium, the preset pressing pressure, the preset pressing time, the preset peeling speed, and the preset peeling angle are sufficient to overcome the adhesion force between the oxide film shell of the liquid metal microdroplets in the liquid metal microstructure master and the liquid metal microdroplets, but less than the adhesion force between the liquid metal microstructure master and the substrate.

[0035] Preferably, the predetermined viscous stretching medium, the predetermined pressing force, the predetermined pressing time, the predetermined peeling speed, and the predetermined peeling angle result in a peeling force generated by the liquid metal microstructure master during the replication operation that is greater than 20% of the bonding force between the oxide film shell layer of the liquid metal microdroplets and the liquid metal microdroplets in the liquid metal microstructure master, but less than 20% of the bonding force between the liquid metal microstructure master and the substrate, thereby forming a peeling force window. Alternatively, a narrower peeling force window range can be selected, for example, greater than 30% of the bonding force between the oxide film shell layer of the liquid metal microdroplets and the liquid metal microdroplets in the liquid metal microstructure master, but less than 30% of the bonding force between the liquid metal microstructure master and the substrate, thereby allowing control over the number of times the liquid metal microstructure master 100 can be peeled off.

[0036] The magnitude of the aforementioned peeling force can be measured, for example, by observing the integrity of the liquid metal microstructure as shown in the SEM image of the replicated liquid metal microstructure 300 obtained from the replication operation, and by the number of times the liquid metal microstructure is completely peeled off. The method proposed in this invention, such as... Figure 1 As shown, a liquid metal microstructure deposited on a TPU film or glass substrate is solidified to form an oxide film shell, serving as a liquid metal microstructure master 100. Polyimide tape (PI tape) is adhered to the surface of the liquid metal microstructure master 100 as an adhesive stretching medium. A given pressing pressure is applied and held for a predetermined time, followed by peeling off the PI tape 200 at a 45° angle. The PI tape 200 is made of polyimide film and silicone adhesive, and is temperature resistant from 260°C to 300°C. The thickness of the PI tape 200 is 0.055 mm, for example, commercially available DuPont Kapton PI tape. Example 1

[0037] This embodiment provides a method for replicating liquid metal microstructures, such as micrometer-sized circuits, on a flexible thermoplastic polyurethane (TPU) film. The replication method specifically includes the following steps: S1: Weigh 20% (by mass) of EGaIn (Ga:In ratio 3:1wt%) and place it in a solvent composed of ethylene glycol (EG), propylene glycol, and water in a ratio of 70:20:10. Disperse the mixture ultrasonically for 5 minutes. Add 5% (by mass) of a polymer solution with a viscosity of 5 cP, such as PVPK30 solution, and mechanically stir at room temperature for 24 hours to obtain the ink. It should be understood that in this step, EG, as the main solvent, facilitates the dispersion of liquid metal; propylene glycol adjusts viscosity and surface tension; and a small amount of water helps in the initial formation of the oxide film shell. The final ratio may need to be fine-tuned based on the actual viscosity, i.e., targeting 5 cP, and for printing stability. In this ink, several liquid metal droplets of approximately 5 μm are formed, suspended in the solvent portion formed by the PVPK30 solution and the mixture of ethylene glycol (EG), propylene glycol, and water.

[0038] S2, the ink is placed into a microfluidic pump and fed into a nozzle with an inner diameter of 100 μm. A clean TPU film is used as the substrate for mounting. The nozzle tip is positioned at a height of 0.5 mm, and a 3.0 kV DC high voltage is applied, causing the nozzle tip to form a stable Taylor cone. The spindle movement is controlled to print a liquid metal microstructure with a linewidth of 100 μm and a thickness of 30 μm, featuring a preset pattern. During printing, the microfluidic pump flow rate is 1.9 μL / min, which can be adjusted within the range of 0.8 to 2.5 μL / min. The corresponding spindle speed, i.e., the printing speed, is 7 mm / s, but this can be adjusted within the range of 5 to 12 mm / s by varying the flow rate.

[0039] S3, allow the TPU film with the liquid metal microstructure to stand for 30 minutes. During partial solvent evaporation, the surface of the liquid metal microdroplets comes into full contact with the air, forming a dense oxide film shell, thus solidifying the liquid metal microstructure to obtain the liquid metal microstructure master template 100. The temperature conditions can be room temperature and the relative humidity 40%RH. The liquid metal microstructure in the liquid metal microstructure master template 100 is as follows... Figure 2 As shown, the liquid metal microstructure exhibits uniform distribution of metal droplets, resulting in high resolution of the printed structure.

[0040] S4. At room temperature, take a PI tape 200, such as DuPont's 0.055mm thick Kapton HN type PI tape, and lay it flat to cover the surface of the oxide film shell. Using a force sensor, apply a uniform pressing pressure of 0.1MPa with precise feedback and hold for 30s to ensure that the adhesive of the PI tape 200 is fully embedded in the oxide film shell. Peel off the PI tape 200 at a 45° angle and a speed of 8mm / s. The peeling process can be recorded synchronously using a force sensor. At this point, at least a portion of the oxide film shell and the liquid metal microdroplets tightly connected to the oxide film shell are obtained on the PI tape 200, which is a part of the liquid metal microstructure master 100. The pattern of this part is consistent with the preset pattern, thus obtaining a replicated liquid metal microstructure 300 with a linewidth of approximately 100μm and smooth edges without obvious burrs. The remaining portion of the liquid metal microstructure master 100, which is completely preserved on the TPU film, still has the same preset pattern, and can therefore be used for second, third, and subsequent replication operations.

[0041] The liquid metal microstructure 300 replicated in Embodiment 1 of this invention is as follows: Figure 3 As shown. Comparison Figure 2 and Figure 3 As can be seen, the liquid metal microstructure master 100 exhibits a discrete, near-spherical particle assembly morphology with clear particle boundaries. These spherical particles are liquid metal droplets with an oxide film shell. In contrast, the replicated liquid metal microstructure 300 transforms into a continuous network morphology, with significantly reduced particle boundaries and localized fusion and pores. This morphological transformation directly demonstrates the technical effect of this invention: utilizing the mechanical difference between the oxide film shell and the internal liquid core, and achieving internal fracture-like replication through a viscous stretching medium. The replicated liquid metal microstructure 300 maintains the macroscopic pattern outline of the liquid metal microstructure master 100, while the pattern of the liquid metal microstructure master 100 is completely preserved. These operational results demonstrate that, under conditions of 0.1 MPa pressing pressure, 45° peeling angle, and 8 mm / s peeling speed, the adhesive force of the PI tape 200 is sufficient to overcome the bonding force between the oxide film shell of the liquid metal microdroplets and the internal liquid metal microdroplets, enabling the fracture and transfer of the internal liquid metal. At the same time, it is less than the bonding force between the liquid metal microstructure master 100 and the TPU substrate, ensuring that the remaining portion of the liquid metal microstructure master 100 retained on the TPU substrate surface still retains the complete preset pattern.

[0042] The remaining portion of the liquid metal microstructure master 100 can be copied. Figure 4 This is a SEM image of the replicated liquid metal microstructure 300 obtained after a second consecutive replication operation under the same replication conditions from the liquid metal microstructure master 100 in Example 1. (Compared to...) Figure 3 Compared to a single-copy structure, Figure 4 The liquid metal microstructure master 100 exhibits a distinct high-porosity honeycomb network morphology, with thinner connecting ligaments and a reduced solid content, yet it still maintains a continuous macroscopic linear pattern outline. This indicates that after multiple 'solidification-adhesion-peeling' cycles, the liquid metal microstructure master 100, despite material loss, can still maintain effective conductive pathways and pattern resolution, fully demonstrating the high stability of the method of this invention and the reusable nature of the liquid metal microstructure master 100. Example 2

[0043] This embodiment provides a method for replicating liquid metal microstructures multiple times consecutively, specifically including the following steps: With the ink remaining unchanged (i.e., still using the ink obtained in S1 of Example 1), but with the nozzle inner diameter set to 150 μm, micrometer lines with a linewidth of approximately 250 μm were fabricated. The voltage was set to 3.5 kV, the printing height to 2 mm, the flow rate to 3.6 μL / min, and the printing speed to 6 mm / s. After curing at room temperature for 40 minutes, a liquid metal microstructure master template 100 was obtained. Hot melt adhesive tape was used for adhesion, with a pressure of 0.1 MPa and a pressing time of 15 s. The template was then peeled off at a 60° angle and a speed of 5 mm / s. The hot melt adhesive tape was replaced, and the adhesion and peeling steps were repeated to obtain a new replicated liquid metal microstructure 300.

[0044] Applying significant pressure ensures full contact between the hot melt adhesive tape and the microwires, while a suitable peel angle effectively prevents the liquid metal microstructure master template 100 from detaching entirely. This liquid metal microstructure master template 100 was replicated five times consecutively. Even after the fifth replication, the microwires maintained an effective conductive path and good pattern resolution, demonstrating the method's extremely high stability and reusability. Example 3

[0045] This embodiment demonstrates a method for replicating liquid metal microstructures without parameter mismatch, specifically including the following steps: With the ink remaining unchanged (i.e., still using the ink obtained in S1 of Example 1), but with the inner diameter of the nozzle set to 150 μm, micrometer lines with a linewidth of approximately 250 μm are fabricated. The same voltage parameters and printing height are set, and the liquid metal micrometer structure master 100 is obtained after curing at room temperature for 40 minutes. PI tape 200 is used for adhesion. PI tape 200 is made of polyimide film and silicone adhesive, such as the aforementioned polyimide substrate combined with an organosilicon pressure-sensitive adhesive layer, which can withstand temperatures from 260°C to 300°C, and has a thickness of 0.055 mm. Different pressing pressures are applied to different parts of the adhesion structure. A force sensor is used to precisely control the magnitude of the pressing pressure, which ranges from 0.01 to 0.5 MPa for 10 seconds. The PI tape 200 is then peeled off at a 45° angle and a speed of 20 mm / s.

[0046] like Figure 5 As shown, when the pressure is too high, the liquid metal microstructure master 100 is excessively adhered to the PI tape 200, resulting in excessive wear and tear and disconnection of the liquid metal microstructure master 100 on the TPU film substrate surface. Furthermore, the replicated liquid metal microstructure 300 obtained on the PI tape 200 also exhibits structural inhomogeneity, leading to... Figure 5 The defects shown in section 400 are: when the pressure is too low, the pattern of the liquid metal microstructure master 100 cannot be accurately replicated; when the speed is too high, the continuity of the replicated liquid metal microstructure 300 pattern is affected.

[0047] It should be understood that in other embodiments, the polymer may also be other types of PVP (polyvinylpyrrolidone), PVA (polyvinyl alcohol), or PEG (polyethylene glycol).

[0048] It should be understood that the ratio of EG, propylene glycol, and water can also be other ratios that can achieve its function.

[0049] It should be understood that other thicknesses and grades of KaptonPI tape can also be used.

[0050] It should be understood that the substrate can be a TPU film or glass.

[0051] Before actual production operations, the relationship between the selected variables—such as different PI tapes 200, pressing pressure, pressing time, peeling speed, and peeling angle—and the resulting peeling force can be experimentally calibrated using the same replication operation. This yields a variable-peeling force relationship curve after the controlled variable experiment. This allows the peeling force to be maintained within an appropriate range—greater than the adhesion force between the oxide film shell of the liquid metal microdroplets and the internal liquid metal microdroplets, and less than the adhesion force between the liquid metal microstructure master 100 and the substrate—especially within the required peeling force range. This ensures satisfactory results for a single replication operation and the required number of replications.

[0052] Once some of these parameters are fixed, such as selecting PI tape 200, peel speed, and peel angle, the liquid metal microstructure proposed in this invention, such as the replication of liquid metal microscale circuits, can be achieved by controlling the pressing pressure and pressing time.

Claims

1. A rapid replication method for liquid metal microstructures prepared by electrohydraulic inkjet printing, characterized in that, Includes the following steps: Prepare a liquid metal ink for electrohydraulic inkjet printing, wherein the liquid metal ink is a mixture of liquid metal, polymer and solvent; Using a non-contact deposition method of electrohydraulic inkjet printing, liquid metal ink is deposited on the surface of a substrate. The substrate moves with a main axis to form a liquid metal microstructure with a preset pattern. The liquid metal microstructure includes liquid metal droplets, and the liquid metal droplets are filled with the polymer and the solvent. A liquid metal microstructure master is obtained by placing the substrate containing the liquid metal microstructure at room temperature for a period of time to solidify. During the solidification process, at least a portion of the solvent evaporates and each liquid metal microdroplet forms an oxide film shell on the surface, and the polymer exists between the oxide film shells. Then, a viscous stretching medium is covered and adhered to the upper surface of the liquid metal microstructure master plate. A preset pressure is applied to the adhered viscous stretching medium to make the viscous stretching medium adhere tightly to the oxide film shell of the liquid metal microdroplets in the top layer of the liquid metal microstructure master plate. Finally, the viscous stretching medium is peeled off from the surface of the liquid metal microstructure master plate, thereby destroying the oxide film shell of the top layer of liquid metal droplets. This results in the oxide film shell and a portion of the liquid metal microstructure master plate with the preset pattern on the surface of the viscous stretching medium, i.e., a replicated liquid metal microstructure with a continuous network morphology. Simultaneously, the remaining portion of the liquid metal microstructure master plate retained on the substrate surface also has the preset pattern. Before covering and adhering the calibrated viscous stretching medium to the surface of the oxide film shell, the relationship between the selection of the viscous stretching medium, the preset pressing pressure, the preset pressing time, the preset peeling speed, and the preset peeling angle and the peeling force is calibrated to ensure that... The peeling force generated by the viscous stretching medium, the preset pressing pressure, the preset pressing time, the preset peeling speed, and the preset peeling angle during the replication operation of the liquid metal microstructure master plate is sufficient to overcome the bonding force between the liquid metal droplets and the oxide film shell in the liquid metal microstructure master plate, but less than the bonding force between the liquid metal microstructure master plate and the substrate; wherein, the viscous stretching medium is covered and adhered to the surface of the liquid metal microstructure master plate; a preset pressing pressure is applied to the adhered viscous stretching medium to make the viscous stretching medium adhere tightly to the surface of the liquid metal microstructure master plate; and finally, the set of steps of peeling the viscous stretching medium from the surface of the liquid metal microstructure master plate is defined as the replication operation.

2. The rapid replication method for liquid metal microstructures prepared by electrofluid inkjet printing according to claim 1, characterized in that, In the liquid metal ink, the mass fraction of EGaIn liquid metal is 20%, the mass fraction of the polymer is PVP, PVA or PEG, and the remainder is solvent; the solvent is composed of EG, propylene glycol and water; the Ga:In ratio in the EGaIn liquid metal is 3:1~4:1wt%; the viscosity of the polymer is 1~10cP.

3. The rapid replication method for liquid metal microstructures prepared by electrofluid inkjet printing according to claim 2, characterized in that, The EGaIn liquid metal is first ultrasonically dispersed in a solvent for 5 minutes to ensure uniform distribution of the EGaIn liquid metal in the solvent. Then, the polymer is added and dissolved in the solvent, and the two are mixed and stirred for 24 hours.

4. The rapid replication method for liquid metal microstructures prepared by electrofluid inkjet printing according to claim 1, characterized in that, The applied voltage in the electrohydraulic inkjet printing method is direct current, with a voltage range of 2.5kV to 4kV, which forms a stable Taylor cone at the tip of the nozzle; the height of the nozzle tip from the substrate ranges from 0.2mm to 3mm; the inner diameter of the nozzle is 100μm to 150μm, and the linewidth of the prepared liquid metal microstructure is 70μm to 300μm; the curing time of the liquid metal microstructure is 20min to 40min.

5. The rapid replication method for liquid metal microstructures prepared by electrofluid inkjet printing according to claim 1, characterized in that, The viscous stretching medium includes hot melt adhesive tape, polyurethane tape, polyethylene tape, or polyimide tape.

6. The rapid replication method for liquid metal microstructures prepared by electrofluid inkjet printing according to claim 1, characterized in that, The pressing force is 0.01~0.1MPa, and the cumulative pressing time is 10~50s; the pressing force is precisely controlled by a force sensor.

7. The rapid replication method for liquid metal microstructures prepared by electrofluid inkjet printing according to claim 1, characterized in that, When peeling off the viscous stretching medium, the angle between the viscous stretching medium and the substrate is 30°~70°; when the angle is greater than 70°, the vertical pulling force is too large, causing the liquid metal micron structure master plate to be lost; when it is less than 30°, if it is a flexible substrate, the transverse shear force can easily cause the substrate to deform.

8. The rapid replication method for liquid metal microstructures prepared by electrofluid inkjet printing according to claim 1, characterized in that, The peeling speed of the viscous stretching medium is 5 mm / s to 10 mm / s.

9. The rapid replication method for liquid metal microstructures prepared by electrofluid inkjet printing according to claim 1, characterized in that, The replication operation is repeated on the remaining portion of the liquid metal microstructure master remaining on the substrate to achieve multiple consecutive replications of the liquid metal microstructure.

Citation Information

Patent Citations

  • Preparation method of large-area surface enhancement raman scattering substrate

    CN103033496A

  • Electrofluid jet printing preparation device and method for liquid metal micron line strain sensor

    CN121131799A